ANALISIS DINAMIKA BAGI HASIL DEPOSITO MUDHARABAH, SUKU BUNGA DAN INFLASI TERHADAP JUMLAH DEPOSITO MUDHARABAH PADA PT. BANK MUAMALAT INDONESIA (2018-2023) - Manzilah, Audiatul; Suprihadi, Suprihadi (RISTANSI: Riset Akuntansi, 2024)
This study aims to analyze the impact of Mudharabah deposit profit-sharing rates, conventional bank interest rates, and inflation on the Mudharabah deposit amount at PT. Bank Muamalat Indonesia from 2018 to 2023. Using a quantitative approach with secondary data from financial reports, the study employed multiple linear regression analysis. The sample consists of quarterly financial data from 2018 to 2023, totaling 24 observations. The results show that while the profit-sharing rate has no significant effect on Mudharabah deposits, the interest rate has a significant positive impact. Inflation does not significantly affect the Mudharabah deposit amounts. This study globally reveals the dynamics of Mudharabah deposits, there by aiding in formulating strategies to enhance the competitiveness of Islamic banks.